2019
DOI: 10.1007/s00412-019-00696-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Pch2 localization determinants reveals a nucleolar-independent role in the meiotic recombination checkpoint

Abstract: The meiotic recombination checkpoint blocks meiotic cell cycle progression in response to synapsis and/or recombination defects to prevent aberrant chromosome segregation. The evolutionarily-conserved budding yeast Pch2 TRIP13 AAA+ ATPase participates in this pathway by supporting phosphorylation of the Hop1 HORMAD adaptor at T318. In the wild type, Pch2 localizes to synapsed chromosomes and to the unsynapsed rDNA region (nucleolus), excluding Hop1. In contrast, in synaptonemal complex (SC)-defective zip1Δ mut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 73 publications
(117 reference statements)
8
33
0
Order By: Relevance
“…A plausible model is that Pch2 TRIP13 -mediated accumulation of unbuckled Hop1 HORMAD in the nucleoplasm leads to a cell cycle delay whereas an accumulation of unbuckled Hop1 HORMAD on chromosomes leads to a checkpoint silencing (Raina and Vader, 2020). Consistent with this model Pch2 TRIP13 executes its checkpoint-activating function when not bound to chromosomes (Herruzo et al, 2019), and Pch2 TRIP13 -dependent action on chromosomal Hop1 HORMAD silences Mek1 CHK2dependent signaling (Subramanian et al, 2016). The proposed action of Pch2 TRIP13 on Hop1 HORMAD is reminiscent of the function of TRIP13 and MAD2 in the spindle checkpoint (Vader, 2015), and nicely explains why pch2 mutations tend to alleviate arrests caused by synapsis defects but often strengthen arrests caused by DNA repair defects (Raina and Vader, 2020).…”
Section: The Role Of Chromosome Architecture In Checkpoint Activationmentioning
confidence: 87%
“…A plausible model is that Pch2 TRIP13 -mediated accumulation of unbuckled Hop1 HORMAD in the nucleoplasm leads to a cell cycle delay whereas an accumulation of unbuckled Hop1 HORMAD on chromosomes leads to a checkpoint silencing (Raina and Vader, 2020). Consistent with this model Pch2 TRIP13 executes its checkpoint-activating function when not bound to chromosomes (Herruzo et al, 2019), and Pch2 TRIP13 -dependent action on chromosomal Hop1 HORMAD silences Mek1 CHK2dependent signaling (Subramanian et al, 2016). The proposed action of Pch2 TRIP13 on Hop1 HORMAD is reminiscent of the function of TRIP13 and MAD2 in the spindle checkpoint (Vader, 2015), and nicely explains why pch2 mutations tend to alleviate arrests caused by synapsis defects but often strengthen arrests caused by DNA repair defects (Raina and Vader, 2020).…”
Section: The Role Of Chromosome Architecture In Checkpoint Activationmentioning
confidence: 87%
“…SC polymerization is dependent on repair of DSBs, and the recruitment of Pch2 is contingent on SC polymerization [19][20][21][22][23][24][25]. The requirement for Pch2 (in combination with reduced Hop1 levels) in mediating checkpoint function observed in both dmc1D and zip1D [25] points to a non-chromosomal role for Pch2 in checkpoint activation [32] in dmc1D and zip1D cells. Thus, these data suggest that, similar to the contribution of Pch2/TRIP13 to SAC activation (i.e., by maintaining sufficient amounts of O-Mad2 to fuel kinetochore based-SAC signaling) [48][49][50][51][52], Pch2 is needed to maintain the levels of ''signalingcompetent'' Hop1 required for incorporation into ''checkpointactive'' chromosomal sites [69].…”
Section: Pch2 and Hop1 Collaborate To Mediate Prophase Checkpoint Functionmentioning
confidence: 97%
“…In a role for Pch2 in synapsis checkpoint function [25,31]. In zip1D cells, Pch2 is not associated with chromosomes, except with nucleolar chromatin, but this pool of Pch2 is unlikely to contribute to checkpoint function [25,32]. The requirement for Pch2 in checkpoint function in zip1D is seemingly at odds with the described antagonistic role of Pch2 toward Hop1/RHMcbased checkpoint signaling that is associated with Zip1-dependent chromosomal recruitment [7,23,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…In the checkpoint-defective yeast zip1Δ dot1Δ mutant, Pch2 is not retained in the nucleolus and instead it distributes throughout chromatin leading to the proposal that regulation of Pch2 nucleolar localization by Dot1 is important for checkpoint function [69,70]. However, more recent studies have demonstrated that the Pch2 protein also localizes in the cytoplasm of yeast cells, and that the presence of Pch2 in the nucleolus is actually dispensable for checkpoint function [71]. In syp-1 worms, PCH-2 is not detected associated to chromatin [47] (Fig 7), but the synapsis checkpoint is active [45] (Fig 6A).…”
Section: H3k79me Regulates a Meiotic Checkpoint In C Elegansmentioning
confidence: 99%